2021
DOI: 10.1111/anae.15369
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive treatments for the management of septic shock – a narrative review of the current evidence

Abstract: Summary Septic shock is a leading cause of death and morbidity worldwide. The cornerstones of management include prompt identification of sepsis, early initiation of antibiotic therapy, adequate fluid resuscitation and organ support. Over the past two decades, there have been considerable improvements in our understanding of the pathophysiology of sepsis and the host response, including regulation of inflammation, endothelial disruption and impaired immunity. This has offered opportunities for innovative adjun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 103 publications
(123 reference statements)
0
3
0
Order By: Relevance
“…Additionally, the evidences on the use corticosteroids in the treatment for COVID-19 rest mainly on their high efficacy as an anti-inflammatory agent and therapy (i.e., in chronic inflammatory disease) [ 260 ]. Recent study also suggested the beneficial role of corticosteroids to reduce mortality in sepsis, alongside with the likely anti-inflammatory actions to reduce the detrimental effects of MPs-mediated inflammation [ 276 ]. Hence, corticosteroids may indirectly aid in reducing the peripherals MPs level which in turn could prevent undesirable progression and/or further adverse effect of the infection particularly towards the onset of CSVD.…”
Section: Proposition and Potential Implications For Covid-19 Related Mps And Risk For Csvdmentioning
confidence: 99%
“…Additionally, the evidences on the use corticosteroids in the treatment for COVID-19 rest mainly on their high efficacy as an anti-inflammatory agent and therapy (i.e., in chronic inflammatory disease) [ 260 ]. Recent study also suggested the beneficial role of corticosteroids to reduce mortality in sepsis, alongside with the likely anti-inflammatory actions to reduce the detrimental effects of MPs-mediated inflammation [ 276 ]. Hence, corticosteroids may indirectly aid in reducing the peripherals MPs level which in turn could prevent undesirable progression and/or further adverse effect of the infection particularly towards the onset of CSVD.…”
Section: Proposition and Potential Implications For Covid-19 Related Mps And Risk For Csvdmentioning
confidence: 99%
“…The current therapeutics for sepsis mainly focus on early empiric antibiotics, fluid resuscitation, and the use of vasoactive drugs, as well as temporary organ support such as mechanical ventilation and renal replacement therapy. Given the lack of high-quality evidence, many treatments based on dysregulation of the host immune response are not routinely applied in clinical practice ( Donovan et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the sepsis pathology progresses, organ dysfunction often occurs and deteriorates into multiple organ failure and death (18,19,20). Sepsis is estimated to be involved in up to 50% of all hospital deaths, and morbidity and mortality remain unacceptably high in septic patients mainly due to the lack of a specific and targeted treatment (21,22,23). Also, mortality has been reported to increase approximately 5% per year for the first five years after discharge due to the long-term health complications of sepsis (24,25).…”
Section: Introductionmentioning
confidence: 99%